Land Grant To Adopted Children, A Court Case Study - Erma, Zetria; Hidayati, Taufika (LEGAL BRIEF, 2023)
A gift is a free and irrevocable gift from one person to another person regarding movable goods through a Notarial deed or immovable goods under a deed from the Land Deed Official (PPAT) while the grantor is still alive. Gifts can only be made on existing objects, in contrast to inheritance which makes it possible to inherit existing assets, for example insurance coverage money. Even though the rules regarding gifts are clear, problems still often arise where heirs do not agree if the heir's assets are gifted to other people who are not related to the heir, including adopted children. Through descriptive analytical research, the article aims to find out the conditions regarding grants and the maximum share that grant recipients are entitled to get even if they are not heirs such as adopted children